Strike Deadlines: Of What Use Are They? - Onabanjo, Idowu; Christopher, Chidi Odogwu (Archives of Business Research, 2017)
This article is intended to be an advocacy paper against setting of strike deadlines before embarking on strikes. In public sector for example, unions have realized that the only language government understands is strike, and when union gives deadlines, government barely takes action to call union to the negotiation table. Rather it embarks on campaign of calumny, which is a way of beating about the bush. This paper illustrates that despite strike deadlines, strikes still occur. This shows that some strikes are unavoidable. This paper gives reasons making some strikes unavoidable despite the huge cost of strikes and the warning given through the deadlines.